2013
DOI: 10.1534/g3.112.005017
|View full text |Cite
|
Sign up to set email alerts
|

Strain Specific Genotype−Environment Interactions and Evolutionary Potential for Body Mass in Brook Charr (Salvelinus fontinalis)

Abstract: Discriminating between genetic and environmental causes of phenotypic variation is an essential requirement for understanding the evolutionary potential of populations. However, the extent to which genetic variation differs among conspecific groups and environments during ontogeny has rarely been investigated. In this study, the genetic basis of body mass was measured in three divergent strains of brook charr (Salvelinus fontinalis) in different rearing environments and at different time periods. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…2011). Often heritability depended on strain, for example heritability of body mass showed mean (± standard error) for domestic, Laval and Rupert strains of 0.61 (± 0.07), 0.37 (± 0.06), and 0.30 (± 0.08), respectively (Crespel et al . 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…2011). Often heritability depended on strain, for example heritability of body mass showed mean (± standard error) for domestic, Laval and Rupert strains of 0.61 (± 0.07), 0.37 (± 0.06), and 0.30 (± 0.08), respectively (Crespel et al . 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…In eastern North America, native Brook Trout demonstrate substantial genetic differentiation even among geographically close populations as well as across major regions of their distribution, which is probably associated with the geography of glacial refugia and postglacial colonization patterns (Angers and Bernatchez 1998;Danzmann et al 1998;Castric et al 2001). Recent studies also showed genetically based differences in terms of growth, gene expression, and energy mobilization among Brook Trout populations from different geographic regions (Bougas et al 2010;Crespel et al 2013aCrespel et al , 2013b. In our study, the broad geographic origins of the four known hatchery sources introduced to Idaho were reflected in significant differentiation from each other with high pairwise F ST values among the four hatchery samples.…”
Section: Discussionmentioning
confidence: 99%
“…; Crespel et al . ) due to the low number of families used (10–36). In total, there were 352 genetic correlation estimates.…”
Section: The Gxe Studies Published During 1964–2013mentioning
confidence: 99%